Improving Special Education Service Delivery Through Interdisciplinary Collaboration. (September 2021) - Dillon, Suzanna; Armstrong, Erika; Goudy, Leah; Reynolds, Hannah; Scurry, Sara
Central to positive learning outcomes for students with disabilities is the ability of the individualized education program (IEP) team to work collaboratively. Within the IEP team, effective service delivery involves direct and related service providers working in an interdisciplinary capacity as they share professional responsibilities to implement the student's program and achieve the common goal of improved student outcomes. With support from the literature, this paper discusses the core components of Bronstein's Interdisciplinary Collaboration Model (2003); and elucidates how professionals share their content knowledge and technical skills with each other, collaborate in instructional design, and gain a firm understanding of each other's discipline in practice. Practical applications that promote interdisciplinary collaboration between adapted physical educators, special educators, related service providers, and parents to improve service delivery and learner outcomes are shared.